Discussion Criminal Offense Of Fraud Committed By Members Of The Indonesian National Army (TNI) - Nainggolan, Yolanda; Esther, July; Sinaga, Jusnizar (Indonesian Journal Publisher, 2025)
Fraud committed by members of the TNI is a very concerning issue because it involves individuals who should be role models in upholding the law and protecting the public. This crime not only undermines public trust but also shows a violation of the code of ethics and military discipline, even though based on their duties the TNI is required to be someone who has high discipline from various aspects.The approach used by the author of this research is the Normative Juridical Approach where this approach is an approach that focuses on the study of library law which is carried out by examining library materials or secondary data as basic material to be researched by conducting a search for regulations related to this problem.The crime of fraud aims to convince the victim to fulfill his wishes. Fraud is not regulated in the Military Criminal Code (KUHPM), but the examination process by members of the TNI is carried out in the Military Court. The settlement of the crime of fraud by members of the Indonesian National Army follows Law No. 31 of 1997, which includes the stages of investigation, prosecution, and implementation of the decision.The verdict on the crime of fraud committed by members of the Indonesian National Army based on Decision Number 41-K/PM.I-02/AD/III/2024 is correct because it is in accordance with applicable laws. The judge stated that the defendant was legally and convincingly proven guilty of committing the crime of fraud by determining the evidence revealed during the trial and also the judge's own belief in the case.